Enhanced CXCR4 Expression of Human CD8Low T Lymphocytes Is Driven by S1P4 - Burkard, Tobias; Dreis, Caroline; Herrero San Juan, Martina; Huhn, Meik; Weigert, Andreas; Pfeilschifter, Josef M.; Radeke, Heinfried H. (Frontiers in Immunology, 2021)
Although the human immune response to cancer is naturally potent, it can be severely disrupted as a result of an immunosuppressive tumor microenvironment. Infiltrating regulatory T lymphocytes contribute to this immunosuppression by inhibiting proliferation of cytotoxic CD8+ T lymphocytes, which are key to an effective anti-cancer immune response. Other important contributory factors are thought to include metabolic stress caused by the local nutrient deprivation common to many solid tumors. Interleukin-33 (IL-33), an alarmin released in reaction to cell damage, and sphingosine-1-phosphate (S1P) are known to control cell positioning and differentiation of T lymphocytes. In an in vitro model of nutrient deprivation, we investigated the influence of IL-33 and S1P receptor 4 (S1P4) on the differentiation and migration of human CD8+ T lymphocytes. Serum starvation of CD8+ T lymphocytes induced a subset of CD8Low ST2L+ cells characterized by enhanced expression of the regulatory T cell markers CD38 and CD39. Both S1P1 and S1P4 were transcriptionally regulated after stimulation with IL-33. Moreover, expression of the chemokine receptor CXCR4 was increased in CD8+ T lymphocytes treated with the selective S1P4 receptor agonist CYM50308. We conclude that nutrient deprivation promotes CD8Low T lymphocytes, contributing to an immunosuppressive microenvironment and a poor anti-cancer immune response by limiting cytotoxic effector functions. Our results suggest that S1P4 signaling modulation may be a promising target for anti-CXCR4 cancer immunotherapy.